2010
DOI: 10.1007/s12275-010-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of insecticidal activity of a bacterial strain, Serratia sp. EML-SE1 against diamondback moth

Abstract: To identify novel bioinsecticidal agents, a bacterial strain, Serratia sp. EML-SE1, was isolated from a dead larva of the lepidopteran diamondback moth (Plutella xylostella) collected from a cabbage field in Korea. In this study, the insecticidal activity of liquid cultures in Luria-Bertani broth (LBB) and nutrient broth (NB) of a bacterial strain, Serratia sp. EML-SE1 against thirty 3rd and 4th instar larvae of the diamondback moth was investigated on a Chinese cabbage leaf housed in a round plastic cage (Ø 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Liquid culture of Serratia sp. EML-SE1 uses as a biocontrol agent to control the diamondback moth, Plutella xylostella (Jeong et al 2010). These combined results demonstrate that this species acts as a bioinsecticidal agent.…”
Section: Discussionmentioning
confidence: 75%
“…Liquid culture of Serratia sp. EML-SE1 uses as a biocontrol agent to control the diamondback moth, Plutella xylostella (Jeong et al 2010). These combined results demonstrate that this species acts as a bioinsecticidal agent.…”
Section: Discussionmentioning
confidence: 75%
“…In the larval gut of other lepidopterous insects, such as the small white butterfly (Pieris rapae L.), Proteobacteria was the most highly represented phylum (Robinson et al, 2010). Because red or pink colored Serriatia were lethal to insect pests when ingested, these dominant bacterial species even could kill their host insect and might be used as an insecticide (Jeong et al, 2010). The larval diet influenced the microbial composition of these lepidopteran insects (Brinkmann et al, 2008;Pinto-Tomás et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al . showed that S. marcescens produces insecticidal oral toxins [122]. Interestingly, there is a synergistic insecticidal effect between S. marcescens chitinases [123] and Bt Cry1Ac toxin [90].…”
Section: Insecticidal Genes and Toxins Shared By Entomopathogenic mentioning
confidence: 99%